CURRENT DEVELOPMENTS ON ANTI-INFLAMMATORY NATURAL MEDICINES - Das, Sayanna; Mandal, Sudip Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
New anti-inflammatory substances are still vitally necessary due to intolerable side effects of the marketed anti-inflammatory drugs; however, the search for the novel entity against inflammation is challenging because of the complexity of the inflammatory process and its role in host defense to infections. Nature is the source of remedies for the mankind. Among the different biological activities of natural products that have been published till date, anti-inflammation is one of the most reported effects. In this review, we have discussed the current (2009–2018) information of some single natural products (quercetin, parthenolide, resveratrol, curcumin, cucurbitacin, capsicin, 1,8-cineole, bromelain, boswellic acid, lyprinol, and coumarin), plant products (garlic, ginger, papaya, blueberry, aloe, broccoli, olive, and rosemary), and non-plant products (marine sponges, mushrooms, and honey) having anti-inflammatory effects. Current information is mainly based on the molecular mechanisms of the above-mentioned products.